The effect of aging on crowded letter recognition in the peripheral visual field - Astle, Andrew T.; Blighe, Alan J.; Webb, Ben S.; McGraw, Paul V. (ARVO, 2014)
Purpose.: Crowding describes the increased difficulty in identifying a target object when it is surrounded by nearby objects (flankers). A recent study investigated the effect of age on visual crowding and found equivocal results: Although crowded visual acuity was worse in older participants, crowding expressed as a ratio did not change with age. However, the spatial extent of crowding is a better index of crowding effects and remains unknown. In the present study, we used established psychophysical methods to characterize the effect of age on visual crowding (magnitude and extent) in a letter recognition task.